(untitled) (Intent Research Scientific Journal, 2025)
This article describes and highlights the organization and specific aspects of the internal audit of commercial banks based on the requirements of international auditing standards, including the features of the application of international standards in bank internal audit, the specific aspects of the process of auditing the financial statements of commercial banks, the organization of internal audit, and the specific aspects of conducting an audit.